Factors Causing The Rise Of Early Childhood Marriage In Indonesia In Terms Of The Marriage Law - Farhan, Afif (Universitas Negeri Semarang, 2023)
This research is motivated by the rise of early marriage that has occurred recently, marriage at age is a national and international problem, where this study aims to find out what are the factors that make underage marriage still common in Indonesia. The method used by the author in compiling this article is the normative method, namely by collecting secondary legal material that is in harmony with the writing of this article. The factors that influence the occurrence of early childhood marriage arise from internal and external factors, besides that the empty space in the provisions of Article 7 of Law 16/2019 is also used by those who are already married, the government and elements of society including religious tokhs, traditional leaders, and students should take part in improving the mindset of the community towards underage marriage, In addition, the author also suggests revising the provisions of articles in the marriage law because underage marriage is very vulnerable for the bride and groom.